a) \(\left|x-2\right|=3\)
\(\Rightarrow\orbr{\begin{cases}x-2=3\\x-2=-3\end{cases}}\Rightarrow\orbr{\begin{cases}x=5\\x=-1\end{cases}}\)
vậy \(\orbr{\begin{cases}x=5\\x=-1\end{cases}}\)
b) \(\left(x+1\right)^3=8\)
\(\left(x+1\right)^3=2^3\)
\(\Rightarrow x+1=2\)
\(\Rightarrow x=1\)
vậy \(x=1\)
c) \(\left(x-1\right)^2=25\)
\(\left(x-1\right)^2=5^2\)
\(\Rightarrow x-1=5\)
\(\Rightarrow x=6\)
vậy \(x=6\)
a/ I x - 2 I = 3
=> x - 2 = 3 hoặc x - 2 = -3
=> Với x - 2 = 3 thì x = 2 + 3 = 5
Với x - 2 = -3 thì x = 2 + (-3) = -(3 - 2) = -1
=> x = 5 hoặc x = -1
b/ ( x + 1 )3 = 8
=> ( x + 1 )3 = 23
=> x + 1 = 2
=> x = 2 + 1
=> x = 3
c/ ( x - 1 )2 = 25
=> ( x - 1 )2 = 52
=> x - 1 = 5
=> x = 5 + 1
=> x = 6
Ơ cho mình xin lỗi câu b nha
( x + 1 )3 = 8
=> ( x + 1 )3 = 23
=> x + 1 = 2
=> x = 2 - 1
=> x = 3